2021
DOI: 10.1038/s41564-020-00849-w
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptation of the small intestine to microbial enteropathogens in Zambian children with stunting

Abstract: Environmental enteropathy is a major contributor to growth faltering in millions of children in Africa and South Asia. We carried out a longitudinal, observational and interventional study in Lusaka, Zambia, of 297 children with stunting (aged 2–17 months at recruitment) and 46 control children who had good growth (aged 1–5 months at recruitment). Control children contributed data only at baseline. Children were provided with nutritional supplementation of daily cornmeal-soy blend, an egg and a micronutrient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 51 publications
0
73
1
5
Order By: Relevance
“…In the context of histopathological features, enteropathogens significantly correlated with chronic inflammation, intra-epithelial lymphocytosis and enterocyte injury. Although we did not find association with villous blunting, a recently published study proposed that in EED, reduced villous surface was a compensatory mechanism to minimize microbial translocation yet, at the cost of impaired growth [ 20 ]. Our group has previously reported greater magnitude of lamina propria T-cell infiltrates and intraepithelial lymphocytes in EED cases as compared to celiac disease in the presence of microbial overgrowth in duodenal aspirate [ 5 ].…”
Section: Discussioncontrasting
confidence: 90%
“…In the context of histopathological features, enteropathogens significantly correlated with chronic inflammation, intra-epithelial lymphocytosis and enterocyte injury. Although we did not find association with villous blunting, a recently published study proposed that in EED, reduced villous surface was a compensatory mechanism to minimize microbial translocation yet, at the cost of impaired growth [ 20 ]. Our group has previously reported greater magnitude of lamina propria T-cell infiltrates and intraepithelial lymphocytes in EED cases as compared to celiac disease in the presence of microbial overgrowth in duodenal aspirate [ 5 ].…”
Section: Discussioncontrasting
confidence: 90%
“…We directly compared environmental enteropathy in three groups: hospitalised children with SAM and persistent diarrhoea, asymptomatic children with stunting unresponsive to nutritional therapy, and apparently healthy adults from a community in which EE is known to be almost ubiquitous. The last two groups were recruited exclusively from the same disadvantaged community (Misisi, Lusaka), and the groups have been described in previous publications [ 16 , 21 , 22 ]. The adults and children from Misisi were in apparently good health; potential participants with clinical illness did not donate samples for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The adults and children from Misisi were in apparently good health; potential participants with clinical illness did not donate samples for this study. The adults were volunteers [21] , and the children had been requested to undergo endoscopy and biopsy in order to search for infections or other explanations for severe acute, or chronic non-responsive, malnutrition [16] . The presence of EE in each group was confirmed using formal morphometry of mucosal biopsies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That study demonstrated that immunohistochemical staining of DUOX2 protein in the villus epithelium distinguished EE biopsies from controls. Given that reduced villus height in EE has been shown to associate with decreased microbial translocation over time (11), it is remarkable that surface mucosal cells scored highly for signatures of both reduced villus height and decreased microbial translocation (as measured by decreased plasma LPS concentrations). This suggests that this cell subset may be associated with adaptive shortening of the villus in response to enteropathogen exposure.…”
Section: Duox2 In Epithelial Remodeling In Eementioning
confidence: 99%